Extramedullary Multiple Myeloma Presenting as a Pituitary Mass Lesion - Dimopoulou, C.; Ormanns, S.; Eigenbrod, S.; Müller-Lisse, U.; Emmerich, B.; Reincke, M. (Experimental and Clinical Endocrinology & Diabetes, 2012)
A plasmocytoma involving the pituitary gland is an extremely rare entity, with approximately 22 cases of solitary myeloma or multiple myeloma presenting with sellar mass reported in the literature so far.Here, we report the case of a 71-year-old female patient affected by an extramedullary IgG-lambda multiple myeloma presenting as a pituitary mass lesion. We summarize the diagnostic approaches that confirmed the diagnosis of multiple myeloma and describe treatment outcome after therapy.Intrasellar plasmocytoma though rare, should be considered in the differential diagnosis of a pituitary mass lesion, since associated with different therapeutic and prognostic implications. Physicians should be alert for intrasellar plasma cell tumors in case of well preserved anterior pituitary function in combination with cranial nerve neuropathies and sellar destruction.
Keywords: extramedullary multiple myeloma; pituitary mass; case report